Gift exchange within a firm: evidence from a field experiment - Charles Bellemare; Bruce S. Shearer (Institute for the Study of Labor (IZA), 2007)
We present results from a field experiment testing the gift-exchange hypothesis inside a tree-planting firm paying its workforce incentive contracts. Firm managers told a crew of tree planters they would receive a pay raise for one day as a result of a surplus not attributable to past planting productivity. We compare planter productivity - the number of trees planted per day - on the day the gift was handed out with productivity on previous and subsequent days of planting on the same block, and thus under similar planting conditions. We find direct evidence that the gift had a significant and positive effect on daily planter productivity, controlling for planter-fixed effects, weather conditions and other random daily shocks. Moreover, reciprocity is the strongest when the relationship between planters and the firm is longterm.
urn:nbn:de:101:1-20080410218
Keywords: 330; Arbeitsvertrag; Anreizvertrag; Leistungsanreiz; Arbeitsproduktivität; Gerechtigkeit; Feldforschung; Forstwirtschaft; Kanada